Coupling coordination degree measurement and spatiotemporal heterogeneity between economic development and ecological environment ----Empirical evidence from tropical and subtropical regions of China. (20th January 2020) - Shi, Tao; Yang, Shenyan; Zhang, Wei; Zhou, Qian
Abstract: Along with the rapid economic development, China's ecological environment is becoming an increasingly severe issue with strong negative externalities accelerating the spatial spillover. This paper uses Geographically and Temporally Weighted Regression (GTWR) to measure and analyze the coupling coordination and spatiotemporal heterogeneity between economic development and ecological environment of 17 tropical and subtropical regions in China from 2003 to 2016. The results show that: First, there is a significant spatiotemporal heterogeneity between economic development and ecological environment; Second, economic development and ecological environment are in an intermediate coupling coordination stage, relative more regions belonged to economic lag type; Third, the ecological lag type mainly lies in developed areas in the east, while the economic lag type is mainly in the central and western regions. Fourth, the spatial relationship and agglomeration effect of economic development are both positive, and the spatial relationship of ecological environment also tends to be positive. Fifth, the interaction relationship between economic development and ecological environment tends to converge. The negative interaction effect of the economic development and ecological environment tends to concentrate in central and eastern developed area, while the positive interaction effect tends to concentrate in central and western developing area. Finally, the paper puts forward corresponding policy recommendations.